Vôlei de “rua” em Cuiabá e os aspectos mediadores da cultura contemporânea - Lima, Caroline Maria de (2018)
This study has as its starting point the cultural and social manifestations of the practice of street volleyball and its bifurcations that gives birth to cultural mediations in its various facets. The object corroborates in investigating the cultural mediations of street volleyball in Cuiabá - MT, in contemporaneity, the cultural aspects contained in the experience of its practice allow a good analysis on the identification, the significance of the value that it has in the life of its agents. The problem of the present research reveals the long and fascinating way to go. What strategies outline the ways of doing "street volleyball" in the city of Cuiabá and Mato Grosso? Therefore, the problem of the present research is to unravel, what are the cultural mediations of contemporaneity found in "street volleyball" in Cuiabá - Mato Grosso? The present qualitative descriptive research is based on reports known as life histories of its agents, a study on the life of an individual or group of individuals, instrument a semistructured interview with open questions, in the form of oral report, inquiries were made in a non-standardized way, being more spontaneous. We have introduced here some final reflections, not conclusions as possibilities for new recognition of the aspects of cultural mediation that street volleyball in CuiabáMT has played in the sports routine of its agents. Considering also the strength of the culture of street sports in the daily life of its practitioners, we can show the routine of its social agents by the power of the same, evidently found in the contemporary world.